Smartphone applications in paediatric radiology: availability and authority. - Shelmerdine, Susan C; Lynch, Jeremy O (Pediatric Radiology, 2015)
Background: With the widespread ownership of smartphones, many health care professionals question the degree to which medically related smartphone applications are reliable.Objectives: To assess the variety of smartphone applications relating to paediatric radiology and the presence of health care professional involvement in their development. As a secondary objective, we explore whether there are gaps within the paediatric radiology app market.Materials and Methods: The most popular smartphone marketplaces (Apple iTunes App Store, Blackberry Mobile Market, Google Play Android Market, Nokia Ovi, Samsung and Microsoft Windows Marketplace) were searched for terms relating to paediatric radiology. Cost, review ratings, number of downloads, health care involvement and target audience were recorded.Results: Nine paediatric radiology applications were found in the Apple iTunes App Store and nine in the Google Play Android Market. The target audiences for all applications were health care professionals. None were available for patients or their caregivers. All applications were reported to have medical expertise in their development.Conclusion: All paediatric radiology applications were developed with the aid of a health care professional. Due to the small number available online, there is a potential gap in the marketplace for further applications in this field, possibly aimed at patients and their families.